ANALYSIS OF MATHEMATICS PROBLEM-SOLVING SKILLS THROUGH PROBLEM-SOLVING IN ELEMENTARY SCHOOL STUDENTS - Nabihah, Marwa; Arrahim, Arrahim; Budianti, Yudi (ATTA`DIB, 2025)
Mathematical problem-solving skills are very important for students at the primary school level, but many students face difficulties in developing these skills. The purpose of this study was to assess the effect of using the Problem-Solving Model on students' mathematical problem-solving skills at the primary school level. The method applied was a Systematic Literature Review (SLR), by reviewing 10 articles published within the last 6 years. The research proved that Problem-Solving Modelling has a positive impact on students' mathematical problem-solving skills by encouraging them to identify problems, design strategies, apply mathematical concepts, and evaluate answers. The model provides an organised structure for students to improve their problem-solving skills efficiently.